Optimasi Ekstraksi DNA Pseudonocardia Carboxydivorans 18A213O1 Menggunakan Kit Ekstraksi Promega dan Qiagen - Abdullah Setiawan, Wawan; Riandani Azzahra, Syifa; Handayani, Kusuma; Setiawan, Andi (Jurnal Jaring SainTek, 2024)
More than 70% of the earth's oceans are known to cover the surface of the earth. High biodiversity makes the ocean a habitat for microorganisms such as tunicates. Tunicates can associate with other microorganisms such as Pseudonocardia carboxydivorans so that they can produce bioactive compounds including antibiotics, pesticides and antitumors. The initial stage to identify a bioactive compound is by isolating DNA. This study aims to determine the optimization of bacterial DNA extraction using promega and qiagen extraction kits. This study consists of 3 treatments, namely rejuvenation, bacterial identification and concentration measurement. The results showed that the optimization of using qiagen extraction kit was relatively superior at 1,989 ng/µl - 2,000 ng/µl with 1 hour. While in the optimization of promega extraction, the resulting purity is 1,500 ng/µl - 1,943 ng/µl with a processing time of 2 hours.